2010
DOI: 10.1097/dbp.0b013e3181ee408e
|View full text |Cite
|
Sign up to set email alerts
|

A Neurodevelopmental Survey of Angelman Syndrome With Genotype-Phenotype Correlations

Abstract: Objective-Angelman syndrome (AS) is a neurodevelopmental disorder caused by a deletion on chromosome 15, uniparental disomy (UPD), imprinting defect, or UBE3A mutation. It is characterized by intellectual disability with minimal speech and certain behavioral characteristics. We used standardized measures to characterize the developmental profile and to analyze genotype-phenotype correlations in AS.Method-The study population consisted of 92 children, between 5 months and 5 years of age, enrolled in a Natural H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
150
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 131 publications
(171 citation statements)
references
References 33 publications
12
150
1
Order By: Relevance
“…Those with identifi ed deletions on chromosome 15q11-q13 are referred to as deletion positive (DP), whereas those presenting other etiologies are labeled deletion negative, or non-deletion (ND). Previous investigators have reported individuals without deletions tend to present stronger cognitive, communicative, and linguistic skills than their counterparts with deletions (Didden, Korzilius, Duker, & Curfs, 2004;Didden et al, 2009;Gentile et al, 2010;Williams et al, 2009). The current investigation compared parents ' reports of AAC use across these two groups.…”
Section: Introductionmentioning
confidence: 92%
“…Those with identifi ed deletions on chromosome 15q11-q13 are referred to as deletion positive (DP), whereas those presenting other etiologies are labeled deletion negative, or non-deletion (ND). Previous investigators have reported individuals without deletions tend to present stronger cognitive, communicative, and linguistic skills than their counterparts with deletions (Didden, Korzilius, Duker, & Curfs, 2004;Didden et al, 2009;Gentile et al, 2010;Williams et al, 2009). The current investigation compared parents ' reports of AAC use across these two groups.…”
Section: Introductionmentioning
confidence: 92%
“…It is notable that overall, the most consistent finding is the uniformly poor expressive language skill in all participants regardless of their molecular sub-class. Since the single common molecular mechanism in all participants is the lack of UBE3A protein in parts of the brain where UBE3A is imprinted, a hypothesis can be developed that UBE3A may be essential in the development of expressive language skills (Gentile et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…1) [7]. While there is variability with each molecular class of AS, in general those with deletion have a more severe phenotype, and those with UPD and imprinting defects a less severe phenotype [2,[8][9][10][11]. The diagnostic algorithm described in Fig.…”
Section: Genetic Etiology and Diagnosismentioning
confidence: 99%
“…Patients with AS with UPD and imprinting defects are predicted to have elevated [9,10,22,23]. One possibility is that the other genes located within 15q11-q13 play significant roles in brain development.…”
Section: Genetic Etiology and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation